Net financial benefits of averting HIV infections among people who inject drugs in Urumqi, Xinjiang, Peoples Republic of China (2005-2010) - Ni Mingjian J; Fu Li; Chen Xue; Hu Xiao; Wheeler Kim (BMC, 2012)
Abstract Background To quantify the contribution of locally implemented prevention programmes in contributing to reductions in treatment and care costs by averting HIV infections among those who inject drugs this study calculates net financial benefit of providing harm reduction programmes using information from services being implemented in Urumqi, Xinjiang Uighur Autonomous Region of China ( between 2005 and 2010). Methods Information was collected to assess cost of providing methadone treatment (MMT) and needle and syringe programmes (NSP). HIV incidence was estimated among people who inject drugs (PWID). HIV infections averted were calculated. Net benefit was assessed by estimating costs of providing prevention programmes and comparing these to the costs of providing care. Results An estimated 5678 (range 3982-7599) HIV infections were averted between 2005 and 2010 and the net financial benefit of providing harm reduction programmes compared to treatment and care costs for HIV infections averted was USD 4.383 million during the same time period. Conclusion These results demonstrate the net and accumulating benefit of investing in harm reduction programmes for PWID in Urumqi. The return on investment progressively increased during the time period studied and it is clear that these cost savings will continue to accrue with the continued implementation of HIV prevention interventions in the community that include harm reduction programmes targeted at PWID.